International strategies in the face of aging population - Drop, Bartłomiej; Jędrych, Marian; Barańska, Agnieszka; Firlej, Ewelina; Janiszewska, Mariola (Polish Journal of Public Health, 2016)
Introduction. Population aging poses many important economic, social, and health challenges to the modern world. This applies mostly to developed countries. The phenomenon requires joint action of Member States of the European Union, the World Health Organization, the United Nations, the Council of Europe as well as some unified strategies for the actions taken by these entities. Aim. The aim of this study was to demonstrate international strategies implemented in the face of demographic changes.  Material and methods. The authors analyzed the documents outlining strategies for both organizations and entities, as well as recommendations for international scientific consultation on strategy of the aging population. Results. Analysis of changes happening to the oldest age groups showed the need for cooperation between countries. An overview of the strategies being taken at the moment and those that had been undertaken previously by international entities can contribute to modify the arrangements of the elderly; in order to improve the living conditions in multidimensional aspect. Conclusions. The key to achieving the desired effect through implementing the policies of individual countries is to monitor them on a regular basis.